Effectiveness and Safety of Atazanavir Use for the Treatment of Children and Adolescents Living With HIV: A Systematic Review - Saint-Lary, Laura; Dassi Tchoupa Revegue, Marc Harris; Jesson, Julie; Renaud, Françoise; Penazzato, Martina; Townsend, Claire L.; O'Rourke, John; Leroy, Valériane; , WHO HIV Hepatitis; STIs (HHS) Department (Frontiers in Pediatrics, 2022)
Background Atazanavir/ritonavir is recommended as a preferred second-line antiretroviral regimen in children older than 3 months, alternatively to lopinavir/ritonavir. We performed a systematic review to assess safety and effectiveness of atazanavir use in children and adolescents. Methods We searched observational studies and clinical trials on Web of Science, Embase and Cochrane CENTRAL database between 2009/01/01 and 2020/10/01; as well as grey literature. We extracted safety (adverse events, grade 3 or 4 adverse events, treatment discontinuation) and effectiveness (CD4 cell counts and HIV viral load) outcomes. We estimated weighted summary pooled incidence with corresponding 95% confidence intervals. Results Out of the 1,085 records screened, we included five studies (one comparative cohort, three single phase 2-3 trial arms, one retrospective cohort) reporting 975 children and adolescents, of whom 56% (544) received atazanavir. Three studies reported all-cause treatment discontinuation rates, yielding a pooled incidence of 19% [15–22] at 12 months. The comparative cohort compared atazanavir to darunavir, with few grade 3–4 adverse events, except transient hyperbilirubinemia, occurring in half (92/188) of the atazanavir patients. No death occurred (two studies reporting). Four studies described increased CD4 cell counts and decreased HIV viral load at 6 or 12 months. Conclusion Few safety and effectiveness data were available for children and adolescents exposed to atazanavir. Transient grade 3–4 hyperbilirubinemia was the main adverse outcome reported. Immune and viral responses were descriptive. The use of atazanavir/ritonavir in children and adolescents needs further investigation, but remains a suitable option for a preferred second-line antiretroviral regimen. PROSPERO number CRD42022309230